Evaluation of polyaniline-Nafion® composite membranes for direct methanol fuel cells durability tests. (6th July 2015) - Escudero-Cid, R.; Montiel, M.; Sotomayor, L.; Loureiro, B.; Fatás, E.; Ocón, P.
Abstract: A Nafion ® membrane has been both electrochemically and chemically modified in-situ to incorporate polyaniline (PANi) into its structure. The proposed objective was to decrease the methanol (MeOH) permeability and thus improve the durability of a direct methanol fuel cell device. Permeability and conductivity of the modified membranes were measured using the unmodified Nafion ® 117 as a reference. The permeability was determined from the electrochemical oxidation of permeated methanol, and the conductivity was determined via electrochemical impedance spectroscopy. To evaluate the effect of these modifications, the performance of a MeOH/O2 single-cell was measured using different MeOH flows and concentrations. The device durability was evaluated under a constant potential and at different operating times. The power density, p, at high MeOH flows and concentrations was 7 times higher for the PANi-modified membrane than the unmodified Nafion ® 117. The durability of the modified membranes containing small amounts of PANi was 2 times higher using low MeOH flows and concentrations, while the power densities were similar. Impedance measurements were performed before and after the long-term durability tests in order to identify the improvements at the different parts of the fuel cell. Highlights: PANi/Nafion ® membranes were prepared by chemical and electrochemical methods. Permeability and conductivity of membranes were determined electrochemically. Higher power density with PANi membranes at high MeOH flow and concentration. Higher durability of PANi membranes at low MeOH flow and concentration.